Moritz Heinrich Romberg (1795–1873): Early founder of neurology. Issue 2 (18th June 2012) - Housman, Brian; Bellary, Sharath S.; Walters, Andrew; Mirzayan, Nadine; Shane Tubbs, R.; Loukas, Marios
<x xml:space="preserve">Abstract</x> Moritz Heinrich Romberg (1795–1873) began his pursuit of neurology in 1820 by translating into German Andrew Marshall's The Morbid Anatomy of the Brain. In 1830, Romberg was hired as Privatdozent of special pathology and therapy in the Charité, the University Hospital of Berlin. He quickly rose to director of the royal clinic in 1845, at which time he wrote Lehrbuch der Nervenkrankheiten des Menschen, a text generally regarded as the first formal treatise on nervous diseases. He identified the role of proprioception in tabes dorsalis, and became the first neurologist to describe the typical pupillary presentation found in patients with tertiary syphilis. Romberg is perhaps most famous for identifying "Romberg's sign, " the distinctive sensory ataxia observed in neuropathies of the dorsal columns. Clin. Anat. 27:147–149, 2014. © 2012 Wiley Periodicals, Inc